Pengaruh Persepsi Kemudahaan terhadap Keputusan Penggunaan Dompet Elektronik Ovo dengan Persepsi Manfaat sebagai variabel Mediasi - Eneng Iviq Hairo Rahayu (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
This study uses a quantitative approach to the survey method. The data used is primary data in the form of a questionnaire totaling 100 respondents. The subject of this research is the Ovo e-wallet user community in Jabodetabek. Data analysis uses a partial least square which has the aim of simplifying the results of processed data, so that it is easy to understand and interpret. The results of this study indicate that Perceived Benefits have a significant influence on Decisions. The path coefficients value shows a positive number of (0.656) which indicates that Perceived Benefits have a positive influence on the decision to use the Ovo e-wallet. Perceived convenience does not have a significant effect on the decision to use the Ovo e-wallet. Perceived convenience does not have a significant effect on the decision to use the Ovo e-wallet. Perceived convenience has a significant influence on perceived benefits